2021
DOI: 10.1088/1755-1315/910/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Purification and Characterization of Transglutaminase From Some Plants

Abstract: The present study aimed to Isolate trans-glutaminase EC:2.3.2.13 from some plants sources and Purified it and Studied it’s Charctarestics as well as it’s practical applications in the production of sausage.The enzyme was extracted from four types of plants (rosemary, chard, radish, arugula) using nine extraction solutions that included distilled water,Sodium chloride 3% solution, sodium chloride 5% solution, sodium phosphate solution 0.1 M and an pH 6.5, sodium phosphate 0.1 M and an pH of 7.5, Tris - Hcl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Transglutaminase is an enzyme that is involved in the catalysis of acyl-transfer reactions between proteins, peptides and amines [29]. Generally, transglutaminase is found in plant and animal tissues [30][31][32]. A study conducted to screen 5000 bacteria from soil samples showed that many soil bacteria have capability of producing transglutaminase.…”
Section: Role Of Microbial Transglutaminasementioning
confidence: 99%
“…Transglutaminase is an enzyme that is involved in the catalysis of acyl-transfer reactions between proteins, peptides and amines [29]. Generally, transglutaminase is found in plant and animal tissues [30][31][32]. A study conducted to screen 5000 bacteria from soil samples showed that many soil bacteria have capability of producing transglutaminase.…”
Section: Role Of Microbial Transglutaminasementioning
confidence: 99%
“…Most of the recent research focused on discovering the Complementary advantages that are obtained through composite films or multi-component films. Where it was observed through the study conducted by the researcher (5) an improvement in the mechanical, barrier and antioxidant properties of the modified whey protein membranes by adding tea extract.…”
Section: Introductionmentioning
confidence: 99%